Deep learning in high schools: exploring pedagogical approaches for transformative education - Agyeman, Nana Yaw Brenya (Universitas Negeri Yogyakarta, 2024)
In today's ever-changing education landscape, fostering deep learning is paramount for transformative education. Teachers play a pivotal role in this endeavor by implementing effective pedagogies that guide students beyond surface-level understanding toward profound learning experiences. This study aimed to explore the effective pedagogical approaches used in schools to promote deep learning within a transformative educational setting. Adopting a qualitative approach with a case study design, the study focused on a single school to investigate these approaches. The study population comprised teachers and learners, with a purposive sample of eight participants, including four teachers and four learners. Data collection utilized semi-structured interviews with predetermined questions for the participants. Thematic analysis was employed to systematically distill meaningful themes and patterns from the collected data. The findings indicated that pedagogical approaches significantly contribute to both deep learning and transformative education, emphasizing active student participation. As a result, schools should adopt effective pedagogical approaches such as group discussions, presentations, and projects to enhance students' learning experiences. The study therefore recommends that learner-centred pedagogies, teaching methods and strategies should be used in schools to foster deep learning of learners.